Penerapan Metode Proyek Dalam Meningkatkan Kemampuan Guru Dalam Pelaksanaan Pembelajaran - Nursal Nursal (JURNAL PENDIDIKAN ROKANIA, 2018)
In accordance with the formulation of the problem then the purpose of this study is to determine whether the Application of Model questions and getting answers Can Improve Teacher Ability in Analyzing SK and KD in SDN 006 ROKAN IV KOTO. The type of research was a school action research (PTS). The population in this study is all teachers in SDN 006 ROKAN IV KOTO which amounts to 14 people and all of them are sampled. From the description of data processing and discussion, it can be concluded that the ability of Teachers in Analyzing SK and KD obtained in the first cycle of 56% with good enough category and in the second cycle increased to 75.4% with good category